2019
DOI: 10.3390/ijms20215445
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factors Targeted by miRNAs Regulating Smooth Muscle Cell Growth and Intimal Thickening after Vascular Injury

Abstract: Neointima formation after percutaneous coronary intervention (PCI) is a manifestation of “phenotype switching” by vascular smooth muscle cells (SMC), a process that involves de-differentiation from a contractile quiescent phenotype to one that is richly synthetic. In response to injury, SMCs migrate, proliferate, down-regulate SMC-specific differentiation genes, and later, can revert to the contractile phenotype. The vascular response to injury is regulated by microRNAs (or miRNAs), small non-coding RNAs that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 95 publications
(107 reference statements)
0
23
0
Order By: Relevance
“…The present paper demonstrated that RORα negatively regulated STAT-3 and further decreased the expression levels of the target molecules of STAT-3. The regulation of biological development involves the regulation of transcription factors, non-coding RNA, DNA modification and other multi-level regulation mechanisms, in which transcription factors and miRNAs are closely associated in the regulatory network (22). The expression levels of miRNAs are regulated by complex transcription factors, and the expression of transcription factors themselves are regulated by miRNAs (23).…”
Section: Discussionmentioning
confidence: 99%
“…The present paper demonstrated that RORα negatively regulated STAT-3 and further decreased the expression levels of the target molecules of STAT-3. The regulation of biological development involves the regulation of transcription factors, non-coding RNA, DNA modification and other multi-level regulation mechanisms, in which transcription factors and miRNAs are closely associated in the regulatory network (22). The expression levels of miRNAs are regulated by complex transcription factors, and the expression of transcription factors themselves are regulated by miRNAs (23).…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Additionally, overexpression of KLF4 has been studied in multiple malignant tumors and has been found to regulate various biological functions, including cell proliferation, survival and metastasis. 11,28,29 We have indicated that KLF4 was a downstream target of miR-7-5p. It has been previously confirmed that miR-9 increased the cell apoptosis in ovarian cancer by directly targeting KLF4.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a type of small (20‒25 nucleotides) non-coding RNAs regulating PTMs. Evidence from several studies has implied that miRNAs are essential factors in the mechanisms of vascular remodeling ( Khachigian, 2019 ). miR-145 is a modulator of VSMC phenotype.…”
Section: Modulations Of Klf5 In Vascular Remodelingmentioning
confidence: 99%